Teaching strategy to strengthen media production competencies from the outset of communication for development - Navarrete Vega, Mabel; Romero González, Rosa María (IE Revista de Investigación Educativa de la REDIECH, 2021)
Around the training of communicators, this study starts from the conviction that it is necessary to strengthen their media production skills from experiences that allow them to understand the integral production process from responsible, critical, and democratic communication. The methodology used is of an exploratory and quantitative nature, with the application of a survey to Communication and Journalism students at the Universidad de Colima, it was sought to know their perceptions on the level of competencies to develop media products from communication for development. The results reflect that, in most of the items on media production and project management, the respondents do not consider themselves capable of acting autonomously. The information obtained allows us to offer a didactic proposal that strengthens skills related to media production such as digital skills, project management, and social responsibility.